1841 Ohio Gen. Stat. 257, ch. 35, § 6 - (:unkn) unknown (My University, 1841)
That if any person or persons shall play bullets, along or across any street in any town or village, within this state; or if any person or persons shall run any horse or horses within the limits of any such town or village; or if any person or persons shall shoot or fire a gun at a target within the limits of any recorded town plat in this state; every person or persons so offending, shall be fined in a sum not exceeding five dollars, nor less than fifty cents.
Keywords: DISCHARGE